Input democracy in the European Union : political representation in inputs to EU executives - Sorace, Miriam (Trinity College (Dublin, Ireland). Department of Political Science, 2017)
The dissertation examines the economic left-right congruence between national parties serving in the 7th term of the European Parliament (2009-2014) and their 2009 voters. It represents an assessment of promissory input representation by national parties serving in the European Parliament. A key innovation of the study is the use of written parliamentary questions to retrieve national parties' preferences in economic policy. The study uses original datasets on MEPs' legislative activities and on written questions' contents, establishing a corpus of over 55,000 texts. Chapter 2 is devoted to the study of written questions' functions in the European Parliament: comparison of rules of procedures and a negative binomial regression analysis of authorship patterns are triangulated with quantitative text classification analysis via the Naive Bayes algorithm and complemented with a survey of Commission civil servants and of Members of the European Parliament.
Keywords: Politics, Ph.D.; PhD Trinity College Dublin, 2017